Cornstarch, all-purpose flour and non-fat dry milk as binders in pork adobo spread - Acacio, Yolanda B; De Leon, Sonia Y. (1965., 1965)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Theis (BSFT)--University of the Philippines Diliman
Keywords: Pork adobo